2018
DOI: 10.1016/j.athoracsur.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Steroids Limit Myocardial Edema During Ex Vivo Perfusion of Hearts Donated After Circulatory Death

Abstract: The addition of methylprednisolone to the perfusion solution minimizes the generation of proinflammatory cytokines and development of myocardial edema during normothermic ex vivo perfusion of hearts donated after circulatory arrest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 28 publications
0
24
1
Order By: Relevance
“…The myocardial functional decline during ESHP has been observed in previous studies [5]; however, the severity of myocyte necrosis and apoptosis that occurs in this context has not been previously characterized. This study found the proportion of TUNEL-positive cells was significantly higher in the myocardium after 12 hours of ESHP compared with in vivo samples; however, the overall frequency of apoptotic cells was low (<1%) and out of proportion to the observed decline in myocardial function over time.…”
Section: Commentmentioning
confidence: 73%
See 2 more Smart Citations
“…The myocardial functional decline during ESHP has been observed in previous studies [5]; however, the severity of myocyte necrosis and apoptosis that occurs in this context has not been previously characterized. This study found the proportion of TUNEL-positive cells was significantly higher in the myocardium after 12 hours of ESHP compared with in vivo samples; however, the overall frequency of apoptotic cells was low (<1%) and out of proportion to the observed decline in myocardial function over time.…”
Section: Commentmentioning
confidence: 73%
“…MYOCARDIAL EDEMA. The heart weight gain (edema formation) during the 12-hour ESHP was calculated as a percentage of the initial heart weight, as described previously [5].…”
Section: Metabolic Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The OCS prime solution is supplemented with methylprednisolone in order to minimize myocardial edema. Donor heart exposure to extracorporeal circulation during ESHP has been shown to elicit an inflammatory response, with a 60-fold increase in pro-inflammatory cytokines observed over a 5-h preservation interval ( 145 ). Methylprednisolone may limit this inflammatory response and minimize the development of myocardial edema ( 145 ).…”
Section: Dcd Heart Transplantationmentioning
confidence: 99%
“…Donor heart exposure to extracorporeal circulation during ESHP has been shown to elicit an inflammatory response, with a 60-fold increase in pro-inflammatory cytokines observed over a 5-h preservation interval ( 145 ). Methylprednisolone may limit this inflammatory response and minimize the development of myocardial edema ( 145 ). Oshima et al have also demonstrated that the suppression pro-inflammatory cytokines during ESHP improves posttransplant myocardial function ( 146 ).…”
Section: Dcd Heart Transplantationmentioning
confidence: 99%